KONFLIK PERAN GANDA PEREMPUAN MENIKAH YANG BEKERJA DITINJAU DARI DUKUNGAN SOSIAL KELUARGA DAN PENYESUAIAN DIRI - -, Apollo; Cahyadi, Andi (Widya Warta, 2012)
This study specifically aimed 1) to determine the relationship between family social support and adjustment to the conflict of dual role of working married women and 2) to determine the differences in the dual role conflict of married women who worked on the level of education. The population of the research was 150 working married women as teachers at St. Bonaventura High School of Madiun and lecturers of Widya Mandala Catholic University of Madiun. The sample was 38 in number consisting of 15 teachers and 23 lecturers. The data were collected through three scales, namely the scale of the dual role conflict of married women who worked, family social support, and adjustment. The data were analyzed using Multiple Linear Regression technique and Independent Sample T-test. The result of the analysis on the first hypothesis showed that there was a negative relationship between family social support and adjustment to the dual role conflict of working married women. It was accepted with a value R = -0.370, R Square = 0.137 or 13.7%, the value of F = 2.781, odds error P = 0.002 (<0.05). T test on each of the independent variables was constant. Family social support variable t count was -0791 with a significance level of 0.000 (<0.05). While, the adjustment variable t count was -0235 with a significance level of 0.005 (<0.05). The result of the analysis on the second hypothesis indicated that there were differences in the dual role conflict of working married women based on their level of education. It was accepted with F value of 4.073, t value of 1.523 with a significance level of 0.000 (â‰¤ 0.05). The mean value of S1 education level was 102,96 and the mean education level of the S2 was 109.40. The higher the education level was the higher the conflict of dual role of working married women would be. Â